Withdrawal from chronic administration of cocaine decreases delta opioid receptor signaling and increases anxiety- and depression-like behaviors in the rat - Perrine, Shane A.; Sheikh, Imran S.; Nwaneshiudu, Chinwe A.; Schroeder, Joseph A.; Unterwald, Ellen M. (Neuropharmacology, 2008)
Chronic administration of cocaine has been shown to attenuate the functional capacity of delta opioid receptors to inhibit adenylyl cyclase activity. Abuse and withdrawal from cocaine in humans is associated with increases in anxiety and depression. Since recent research supports the role of delta opioid receptors in anxiety- and depression-like behaviors in rodents, we hypothesized that functional desensitization of delta opioid receptors contributes to anxiety- and depression-like behavioral phenotypes following short-term withdrawal from chronic administration of cocaine. To test this hypothesis, delta opioid receptor signaling and behaviors were evaluated 24 h after 14 days of binge-pattern cocaine administration (15 mg/kg three times daily at 1 h intervals) in male Sprague–Dawley rats. Results showed that the inhibition of adenylyl cyclase by delta opioid receptor agonists was attenuated in the frontal cortex, nucleus accumbens and caudate putamen 24 h after cessation of cocaine administration. One day withdrawal from chronic administration of cocaine resulted in increased anxiety- and depression-like behaviors as measured by the elevated plus maze and the forced swim test respectively, and no change in locomotor activity. The anxiety- and depression-like behaviors were dose-dependently reduced by acute administration of the selective delta opioid receptor agonist, SNC80. These results demonstrate that early withdrawal from cocaine resulted in increased anxiety and depression, which accompanies the desensitization of delta opioid receptor function. Furthermore, cocaine-induced anxiety- and depression-like behaviors were reversible by the delta opioid receptor agonist SNC80.